Readability of consent forms in veterinary clinical research. (22nd February 2019) - Sobolewski, Josey; Bryan, Jeffrey N.; Duval, Dawn; O'Kell, Allison; Tate, Deborah J.; Webb, Tracy; Moore, Sarah
Abstract : Background: "Readability" of consent forms is vital to the informed consent process. The average human hospital consent form is written at a 10th grade reading level, whereas the average American adult reads at an 8th grade level. Limited information currently exists regarding the readability of veterinary general medical or clinical research consent forms. Hypothesis/Objectives: The goal of this study was to assess the readability of veterinary clinical trial consent forms from a group of veterinary referral centers recently involved in a working group focused on veterinary clinical trial review and consent. We hypothesized that consent forms would not be optimized for client comprehension and would be written above the National Institutes of Health‐recommended 6th grade reading level. Animals: None. Methods: This was a prospective study assessing a convenience sample of veterinary clinical trial consent forms. Readability was assessed using 3 methods: the Flesch‐Kincaid (F‐K) Grade Level, Flesch Reading Ease Score (FRES), and the Readability Test Tool (RTT). Results were reported as mean (±SD) and compared across specialties. Results: Fifty‐three consent forms were evaluated. Mean FRES was 37.5 ± 6.0 (target 60 or higher). Mean F‐K Grade Level was 13.0 ± 1.2 and mean RTT grade level was 12.75 ± 1.1 (target 6.0 or lower). There was substantial agreement between F‐K and RTT grade level scores (intraclass correlation coefficient 0.8). Conclusions and Clinical Importance: No form evaluated met current health literacy recommendations for readability. A simple and readily available F‐K Microsoft‐based approach for evaluating grade level was in substantial agreement with other methods, suggesting that this approach might be sufficient for use by clinicians and administrators drafting forms for future studies.